Análisis financiero de las empresas del departamento de Boyacá (2011-2013) (2016)
Article allows viewing, an investigation of the financial situation of different sectors of the department of Boyacá, through vertical and horizontal analysis and financial indicators (liquidity, activity, debt, profitability),which show their financial reality, to determine what strengths and weaknessesexist in these sectors. The information was obtained from the data supplied by companies from Boyacá to the Superintendence of Companies between 2011 and 2013, which will allow us to establish a financial study structurally and different formalities of the sectors to evaluate according to the nature of its activity. The methodology developed in this study is mixed because it has a quantitative component where analysis, ratios or financial indicators will be built and a qualitative component as these data will be analyzed in different sectors.